Effective Writing for Health Professionals: A Practical Guide to Getting Published, 1st edition - Johnstone, Megan-Jane (Routledge, 2020)
Health professionals are increasingly expected to conduct and publish their research, apply for grants, write newsletters, liaise with the media, present conference papers and contribute articles to professional journals.